Evaluation and Demonstration of Different Feeding options for Borana Cattle Fattening - Aman Gudeto; Tesfaye Alemu T; Genet Dadi; Ashebir Worku; Mieso Guru; Frehiwot Mesele (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2020)
Evaluation and demonstration study was conducted at Kemo-Gerbi kebele of Adami Tulu Jidokombolcha district on two to three year old Borana bulls with the objectives of evaluation and demonstration of bulls fattening technologies at on-farm level. One Farmer's Research Extension Group (FREG) was formed for fattening the bulls. Twenty bulls were purchased from Borana zone by farmers for the fattening trials. Two feeding treatments (T1= crushed maize grain (20%) + wheat bran (45%) + 35% Noug seed cake and T2 = wheat bran (65%) + cotton seed cake (35%)) were evaluated at on- farm. Eight hour grazing was common for both treatments. The animals were randomly assigned for dietary rations and data on live weight change of the animals were taken using weight chart tape (developed by JICA project).  Finishing weights, total weight gain and daily weight gain of the bulls were not different (P>0.05) between the treatments. Bulls fed on treatment one attained an average daily weight gain of 0.83 kg per bull; while bulls fed on treatment two gained 0.76 kg per bull per day. Total gross margin of treatment one (53,154.5 ETB) was higher than treatment two (49,467.75 ETB). Cost-benefit analysis showed that feeding option number one (T1) is more profitable than bulls fed on T2.  However, fatteners can use any of the feeding options depending on availability of the ingredients in their area.